Studies on Emblica officinalis Derived Tannins for Their Immunostimulatory and Protective Activities against Coccidiosis in Industrial Broiler Chickens. (22nd January 2014) - Kaleem, Qari Muhammad; Akhtar, Masood; Awais, Mian Muhammad; Saleem, Muhammad; Zafar, Muddassar; Iqbal, Zafar; Muhammad, Faqir; Anwar, Muhammad Irfan
Abstract : The present study reports the effect of Emblica officinalis (EO) derived tannins on humoral immune responses and their protective efficacy against Eimeria infection in chickens. Tannins were extracted from EO and characterized by HPLC. EO derived tannins (EOT) and commercial tannins (CT) were orally administered in broiler chicks in graded doses for three consecutive days, that is, 5th-7th days of age. On day 14 after administration of tannins, humoral immune response was detected against sheep red blood cells (SRBCs) by haemagglutination assay. Protective efficacy of tannins was measured against coccidial infection, induced by Eimeria species. Results revealed higher geomean titers against SRBCs in chickens administered with EOT as compared to those administered with CT and control group. Mean oocysts per gram of droppings were significantly lower (P < 0.05 ) in EOT administered chickens as compared to control group. Lesion scoring also showed the lowest caecal and intestinal lesion score of mild to moderate intensity in chickens administered with EOT. Further, significantly higher (P < 0.05 ) daily body weight gains and antibody titers were detected in EOT administered chickens as compared to those of CT administered and control groups. EOT showed the immunostimulatory properties in broilers and their administration in chickens boost the protective immunity against coccidiosis.